UTILIZING GRAMMARLY IN EVALUATING ACADEMIC WRITING: A NARRATIVE RESEARCH ON EFL STUDENTS’ EXPERIENCE - Muhamad Nova (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
With the development of technology, any writer now can easily check their academic writing with automated writing evaluation program. Though, the utilization of this program may bring both benefits and drawbacks. Thus, a consideration of its strengths and weaknesses is needed. To fill the need, this study aimed to identify the strengths and weaknesses of Grammarly program as an automated writing evaluation program in evaluating academic writing. Using a narrative inquiry in exploring three Indonesian postgraduate students’ experiences by conducting interview and documentation, the result showed that this program has provided useful color-coded feedback with explanation and example, ease of account access, high rate of evaluation speed, and free service for evaluating academic writing. However, some caveats were also found in this program utilization, such as several misleading feedbacks, weaknesses on detecting the type of English and reference list, and lack of context and content evaluation experienced, which became the weaknesses of this program. Further investigation on the efficiency of the feedback given by Grammarly in improving students’ writing quality is needed.